Enhanced aesthetics with all ceramics restoration - Sanjna Nayar; U Aruna; Wasim Manzoor Bhat (Wolters Kluwer Medknow Publications, 2015)
The demand for the dentist to achieve excellence in esthetics and function has driven modern advances in materials and restoration fabrication. The development of various casting alloys and precise casting systems has contributed to the successful use of metal-based restorations. However, patient requests for more aesthetic and biologically "safe" materials that have led to an increased demand for metal-free restorations. The following case presentation illustrates a successful aesthetic and functional application of this exciting computer-aided design/computer-aided manufacturing-digital zirconia-based system for a natural smile.